Correlation of Urine Leukocytes and Urine Bacteria Using Current Sitometry Using Urine in Patients of Children Channel Infection - Adriyani Amin1, IGAA Putri Sri Rejeki1, Ninik Soemyarso Asmaningsih1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Urinary tract infection (UTI) in children is a common illness. The gold standard for UTI diagnosis is urine culture, but it takes a long time and often gives negative results. Currently developed a method of flow cytometry for checking urine sediments. This tool is able to detect leukocytes urine and urine bacteria in quick time. The purpose of this study is to analyze the relationship of urine leukocyte count and the number of urine bacteria using flow cytometry with urine culture in patients with UTI Method: Eighty-four patients were enrolled in this study that consisting of 43 patients with suspected UTI and 43 patients with non-ISK treated at Inpatient Installation, Emergency Installation Department of Health Sciences at Dr.Soetomo General Hospital, Surabaya for 4 months. The examination of urine leukocytes and urine bacteria was using current cytometry method (UF-500i, Sysmex, Japan). While, examination of urine culture using blood agar plate and Mac. Conkey. Results: There was a significant relationship between the number of leukocytes and the number of colonies. The relationship between leukocytes and the number of colonies was weak, this was indicated by Spearman correlation coefficient (rho) value of 0.376. There was a significant relationship between bacteria and the number of colonies. p <0.05. The relationship between the number of urine bacteria and the number of colonies was quite strong indicated by rho = 0.729. Conclusion: There was a relationship between urine leukocyte count and the number of urine bacteria using flow cytometry with a urine culture.